Paraganglioma in pregnancy: A case series and literature review. (March 2022) - Eccles-Smith, Jade; Hopkins, Stephanie; Conn, Jennifer; Johnston, Stephanie; Szabo, Rebecca; Price, Sarah; Nankervis, Alison
Paragangliomas are rare neuroendocrine neoplasms which are often catecholamine-secreting and associated with familial syndromes. Described here are three women with a variety of pathology: isolated secretory paraganglioma diagnosed in pregnancy, secretory metastatic paraganglioma in pregnancy and non-secretory metastatic paraganglioma in pregnancy. Whilst paragangliomas are associated with morbidity and mortality during pregnancy, good maternal and fetal outcomes can be achieved through individualised care within the context of a multidisciplinary team. Although paragangliomas are associated with morbidity and mortality in pregnancy, good maternal and fetal outcomes can be achieved through individualised care within the context of a multidisciplinary team.